THE VARIETIES OF MIGRAINE IN PATIENTS WITH SLEEP DISORDERS AND VEGETARIANS - Amonova Zakhro Kakhramonovna; Murodov Muzaffar Niyozbek o`g`li; Amonova Zilola Kakhramonovna (Western European Studies, 2025)
Migraine is a common neurological disorder characterized by recurrent headaches, often accompanied by nausea, vomiting, and sensitivity to light and sound. Sleep disorders, including insomnia, obstructive sleep apnea (OSA), and restless leg syndrome, have been frequently reported in migraine patients. The interconnection between these two conditions suggests a bidirectional influence where poor sleep can trigger migraines, while migraines can further disrupt sleep. The significance of this study lies in its potential to provide valuable insights into the shared pathophysiology between migraine and sleep disorders, as well as to offer a targeted approach to treatment. Analyzing how sleep disturbances contribute to migraine progression can help healthcare professionals tailor more effective interventions. Additionally, understanding the role of neurochemical changes, such as fluctuations in serotonin and melatonin levels, could lead to improved pharmacological and non-pharmacological treatment options.
Keywords: Vegetarians; migraine; sleep disorders; comorbidity